Pengembangan dan Implementasi Platform E-Commerce untuk Penjualan Dental unit Berbasis Website Menggunakan Model Prototyping - Bagus Sajiwo Bagus (Jurnal Sistem Informasi Komputer ( SIKOM ), 2024)
Abstract—The development of information technology encourages businesses in the healthcare sector, particularly dental unit companies, to utilize digital platforms in order to improve efficiency and expand marketing reach. Conventional dental unit sales processes often cause challenges in data management, limited product information, and low service effectiveness for customers. This study aims to develop and implement a website-based e-commerce platform as a medium for dental unit sales using the prototyping development model. The prototyping method is chosen because it can dynamically accommodate user requirements through stages of requirement gathering, prototype development, user evaluation, sistem refinement, and implementation. The developed platform provides features such as product catalogs, online ordering, customer data management, sales transactions, and sales reports. The results of this study indicate that the implemented e-commerce platform improves accessibility to product information, accelerates transaction processes, and supports more effective and structured sales management. Therefore, the application of a website-based e-commerce platform using the prototyping model can be an appropriate solution to support the digitalization of dental unit sales. Keywords: e-commerce dental unit website prototyping sales information sistem.